Embracing complexity: Exploring the silent struggle of life insurance agents - Tantri Keerthi Dinesh; Ankitha Shetty; Shweta TS; Rashmi Yogesh Pai; Adithya D Shetty (Cogent Business & Management, 2023)
Drawing on Lazarus and Folkman's transactional stress theory, this study aims to explore a broader range of what constitutes work stress among life insurance agents and their needs for organisational work stress prevention. Face-to-face interviews were conducted with life insurance agents (n = 45) that focused on their stress experiences and needs regarding the prevention of work stress. Performing thematic analysis, topics, and themes were extracted from the verbatim transcribed interviews using Atlas.ti. Respondents located the stress factors that affected their mental health which should be targeted for prevention. Various themes were extracted, falling under job responsibilities, handling customers and maintaining long-term relationships, work pressure, mental health indicators, and measures to handle stress. The findings of this research specified that life insurance agents have multifaceted work stress prevention needs where mapping this could facilitate intervention implementation. The agents were explicit about the causes of stress emerging due to relationship between the individual and the challenging environment, leading to Litigation Stress Syndrome. This study sets a platform for the insurance sector to take necessary steps in helping the agents to mitigate stress and cultivating an innovative habit of mindful selling in them by implementing mindfulness interventions.
Keywords: 650; litigation stress syndrome; mental health; mindful selling; work stress; work stress prevention